2007
DOI: 10.5194/hessd-4-125-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A distributed stream temperature model using high resolution temperature observations

Abstract: Abstract. Highly distributed temperature data are used as input and as calibration data for a temperature model of a first order stream in Luxembourg. A DTS (Distributed Temperature Sensing) fiber optic cable with a length of 1500 m is used to measure stream water temperature with a spatial resolution of 0.5 m and a temporal resolution of 2 min. With the observations four groundwater inflows are found and quantified (both temperature and relative discharge). They are used as input for the distributed temperatu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
159
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(162 citation statements)
references
References 19 publications
3
159
0
Order By: Relevance
“…Based on the observed temperature profiles, Schmidt et al (2006) The observed spatial heterogeneity was assumed by Kalbus et al (2008a,b) to result from the permeability distribution of the connected aquifer. Even though observed streambed temperatures are temporally highly variable (e.g., Westhoff et al, 2007), the temperature distribution observed at a certain point in time is a consequence of the spatial distribution of subsurface permeabilities and the head and temperature gradient between groundwater and stream at the time of observation. As long as the temperature observations are recorded at a sufficient depth below the streambed surface, they are not influenced by diurnal temperature oscillations in the surface water and the system can be considered to be at a quasi-steady state for the short duration of observation .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the observed temperature profiles, Schmidt et al (2006) The observed spatial heterogeneity was assumed by Kalbus et al (2008a,b) to result from the permeability distribution of the connected aquifer. Even though observed streambed temperatures are temporally highly variable (e.g., Westhoff et al, 2007), the temperature distribution observed at a certain point in time is a consequence of the spatial distribution of subsurface permeabilities and the head and temperature gradient between groundwater and stream at the time of observation. As long as the temperature observations are recorded at a sufficient depth below the streambed surface, they are not influenced by diurnal temperature oscillations in the surface water and the system can be considered to be at a quasi-steady state for the short duration of observation .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these DTS data have been used to quantify groundwater inflows in streams [Selker et al, 2006b], test temperature model predictions [Westhoff et al, 2007], measure snowpack base temperatures , and measure the groundwater component of a tidal system on a salt marsh [Moffett et al, 2008]. Many of the current applications in surface water have been conducted in water bodies where the effects of solar radiation may not be a concern (e.g., lake bottoms).…”
Section: Introductionmentioning
confidence: 99%
“…An energy balance approach model, after Westhoff et al (30), is used to simulate the temperature in the stream. The model takes into account the following fluxes: solar radiation, longwave radiation, streambed conduction, latent heat (evaporation), and sensible heat (convection).…”
Section: Methodsmentioning
confidence: 99%